Social Conflict Resolution Among Islamic Ideologies in Puger, Jember, East Java - Umiarso Umiarso; Asnawan Asnawan (Jurnal Dialog, 2022)
This research is developed on the basis of analytical construction focusing on two ideologies in Islam, namely Sunni, and Shi’ite. These two mainstreams of school of thoughts often create social conflict in the region of Puger. This research attempts to offer practical solutions. To explore deep understanding, a phenomenological approach involves eight participants, consisting of religious leaders, government officials, and community leaders. An in-depth interviews is used for the main data collection, such as the interview protocol instrument. All data are analyzed by data reduction theory, starting with identifying, determining, and narrating. This study has found that there are some factors trigger the conflict between two groups in the region of Puger including religious sect differences, rivalry existence in pesantren (Islamic boarding school), provocateurs, and allegations of discrimination against particular ideologies. Additionally, this study also affirms that there are other ideologies involved in this conflict. This study suggests intensive communication among the communities in the region of Puger, Jember, East Java, could potentially reduce the issues. Keywords: Islamic ideologies, social conflict, resolution, rivalry